Safety, Pharmacokinetic, and Efficacy Studies of Oral DB868 in a First Stage Vervet Monkey Model of Human African Trypanosomiasis - Thuita, John K.; Wolf, Kristina K.; Murilla, Grace A.; Liu, Qiang; Mutuku, James N.; Chen, Yao; Bridges, Arlene S.; Mdachi, Raymond E.; Ismail, Mohamed A.; Ching, Shelley; Boykin, David W.; Hall, James Edwin; et al. (PLoS neglected tropical diseases, 2013)
There are no oral drugs for human African trypanosomiasis (HAT, sleeping sickness). A successful oral drug would have the potential to reduce or eliminate the need for patient hospitalization, thus reducing healthcare costs of HAT. The development of oral medications is a key objective of the Consortium for Parasitic Drug Development (CPDD). In this study, we investigated the safety, pharmacokinetics, and efficacy of a new orally administered CPDD diamidine prodrug, 2,5-bis[5-(N-methoxyamidino)-2-pyridyl]furan (DB868; CPD-007-10), in the vervet monkey model of first stage HAT. DB868 was well tolerated at a dose up to 30 mg/kg/day for 10 days, a cumulative dose of 300 mg/kg. Mean plasma levels of biomarkers indicative of liver injury (alanine aminotransferase, aspartate aminotransferase) were not significantly altered by drug administration. In addition, no kidney-mediated alterations in creatinine and urea concentrations were detected. Pharmacokinetic analysis of plasma confirmed that DB868 was orally available and was converted to the active compound DB829 in both uninfected and infected monkeys. Treatment of infected monkeys with DB868 began 7 days post-infection. In the infected monkeys, DB829 attained a median C(max) (dosing regimen) that was 12-fold (3 mg/kg/day for 7 days), 15-fold (10 mg/kg/day for 7 days), and 31-fold (20 mg/kg/day for 5 days) greater than the IC50 (14 nmol/L) against T. b. rhodesiense STIB900. DB868 cured all infected monkeys, even at the lowest dose tested. In conclusion, oral DB868 cured monkeys with first stage HAT at a cumulative dose 14-fold lower than the maximum tolerated dose and should be considered a lead preclinical candidate in efforts to develop a safe, short course (5-7 days), oral regimen for first stage HAT.